Investigating the preferred learning styles of male students in English language classrooms at SMK Methodist (ACS) Melaka / Nurul Syahida Abdullah - Abdullah, Nurul Syahida (Faculty of Education, 2010)
Research and studies in the area oflearning styles provide significant insights and suggestions to teachers and curriculum designers in improving the language learning environment and performance ofthe students. The study was conducted to investigate the preferred learning styles ofthe male leamers, and also the use ofprefened learning styles of male learners across age levels. This study thus adopted the Index of Learning Styles (lLS) questionnaire developed by Felder and Soloman in 1991. The findings of the study indicated that the male students preferred Active, Sensing, Visual and Sequential learning styles over Reflective, Intuitive, Verbal and Global learning styles. This shows that the male students prefer to learn through active experimentation and physical activities, drills, visual representations and by focusing on the details. The study also found that the male students' use of learning styles varied across age levels and across dimensions. This implies that the male students develop their prefened learning styles either because they are accustomed to the repeated use of the teachers' teaching styles, or because they find the teaching styles of the teacher as uninteresting. This study implicates that it is important for teachers to recognize the preferred learning styles of the male learners, and match their teaching style with the learning styles to help improve the male learners' competence in the English language classrooms.